Implementing a Multifaceted Intervention to Decrease Central Line–Associated Bloodstream Infections in SEHA (Abu Dhabi Health Services Company) Intensive Care Units: The Abu Dhabi Experience. (14th April 2015) - Latif, Asad; Kelly, Bernadette; Edrees, Hanan; Kent, Paula S.; Weaver, Sallie J.; Jovanovic, Branislava; Attallah, Hadeel; de Grouchy, Kristin K.; Al-Obaidli, Ali; Goeschel, Christine A.; Berenholtz, Sean M.
<x content-type="archive" xml:space="preserve">Abstract</x> OBJECTIVE To determine whether implementation of a multifaceted intervention would significantly reduce the incidence of central line–associated bloodstream infections. DESIGN Prospective cohort collaborative. SETTING AND PARTICIPANTS Intensive care units of the Abu Dhabi Health Services Company hospitals in the Emirate of Abu Dhabi. INTERVENTIONS A bundled intervention consisting of 3 components was implemented as part of the program. It consisted of a multifaceted approach that targeted clinician use of evidence-based infection prevention recommendations, tools that supported the identification of local barriers to these practices, and implementation ideas to help ensure patients received the practices. Comprehensive unit-based safety teams were created to improve safety culture and teamwork. Finally, the measurement and feedback of monthly infection rate data to safety teams, senior leaders, and staff in participating intensive care units was encouraged. The main outcome measure was the quarterly rate of central line–associated bloodstream infections. RESULTS Eighteen intensive care units from 7 hospitals in Abu Dhabi implemented the program and achieved an overall 38% reduction in their central line–associated bloodstream infection rate, adjusted at the hospital and unit level. The number of units with a quarterly central line–associated bloodstream infection rate of less than 1 infection per 1, 000 catheter-days increased by almost 40% between the baseline and postintervention periods. CONCLUSION A significant reduction in the global morbidity and mortality associated with central line–associated bloodstream infections is possible across intensive care units in disparate settings using a multifaceted intervention. Infect. Control Hosp. Epidemiol. 2015;36(7):816–822